BUSINESS STRATEGY DEVELOPMENT IN VISUAL COMMUNICATION DESIGN BUSINESS FOR REFINE EDGE BRANDING IDENTITY STUDIO - Rudhidiptya Yoscar, Diwangkara
Refine edge is a service that runs in the field of visual communication design, located in the city of Bandung. Refine edge has been running since 2018 when it was first established. At that time, the team consisted of only a few designers and freelancers in the visual communication industry. Initially, the company concentrated in the fields of layout and house graphics. On the journey, seeing the development of mid-sized businesses that began to rise in current made refine edge founders present as problem solvers of medium-sized business owners in solving visual communication problems the company have.